2015
DOI: 10.1177/1091142115571578
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the 1997 Expenditure Decentralization Reform in Mexico

Abstract: This article studies the Mexican state-level impact on health outcomes of the decentralization of health funding and responsibilities that took place in 1997. Since the reform took place simultaneously in all states, we focus on a difference in difference estimation of whether those states that received more funds achieved better health outcomes after health services decentralization. According to our results, those states that received more funds did not boost the advances in health outcomes already achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…More than half of the studies reported beneficial effects of decentralization in reducing infant and postneonatal mortality . Two studies did not find significant associations . Interestingly, 2 studies from Brazil and another 2 studies from China reported contradicting results between them.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…More than half of the studies reported beneficial effects of decentralization in reducing infant and postneonatal mortality . Two studies did not find significant associations . Interestingly, 2 studies from Brazil and another 2 studies from China reported contradicting results between them.…”
Section: Resultsmentioning
confidence: 96%
“…Table reports the characteristics of the articles selected for review. Sixteen different studies were identified, with the earliest one published in 2003 and the most recent one published in 2016 . The selected studies were situated in Latin America ( n = 8), Asia ( n = 5), Africa ( n = 2), and multiple countries ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations